2018
DOI: 10.1159/000495638
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestation, Management and Prognosis of Acute Myocardial Infarction in Autosomal Dominant Polycystic Kidney Disease

Abstract: Background/Aims: Cardiovascular complications are the most common cause of death in individuals with autosomal dominant polycystic kidney disease (ADPKD), yet there is no substantial data concerning the clinical characteristics of acute myocardial infarction (AMI) in this population. This study thus aimed to investigate AMI in persons with ADPKD. Methods: A retrospective analysis of ADPKD patients admitted to our hospital over a 13 year period was conducted. Age and gender-matched control patients without ADPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In conclusion, our studies indicated fibrosis in Pkd2-KO hearts. Fibrosis in the conduction system might results in arrhythmia, and thus the PKD patients might be susceptible to atrial fibrillation (12) and potential arrhythmia-induced sudden cardiac death (47). Our studies implicated that cardiac fibrosis was also contributed to systolic and diastolic dysfunctions, which are seen in PKD patients (48).…”
Section: Discussionmentioning
confidence: 64%
“…In conclusion, our studies indicated fibrosis in Pkd2-KO hearts. Fibrosis in the conduction system might results in arrhythmia, and thus the PKD patients might be susceptible to atrial fibrillation (12) and potential arrhythmia-induced sudden cardiac death (47). Our studies implicated that cardiac fibrosis was also contributed to systolic and diastolic dysfunctions, which are seen in PKD patients (48).…”
Section: Discussionmentioning
confidence: 64%
“…When a CVE occurs, it is expected to be more severe than in the general population. A study that analyzed episodes of acute myocardial infarction showed that patients with ADPKD had a higher rate of ST-segment elevation, multi-vessel involvement, and secondary sudden death [16]. However, most studies have focused on the evaluation and progression of CKD [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Two large cohort studies, from China and Taiwan, reported a >2-fold higher incidence of myocardial infarction in patients with ADPKD, which was associated with increased severity of coronary disease and poorer cardiovascular outcomes compared with non-ADPKD controls. 116 , 117 In particular, Yang et al. 117 showed that those with ADPKD had a higher incidence of ST-elevation myocardial infarction (75% compared with 59%), sudden cardiac death (11.5% vs. 4.6%), need for coronary artery bypass grafting (7.7% vs. 5.4%) and higher overall mortality (13.5% vs. 6.2%).…”
Section: Cardiac Manifestations In Adpkdmentioning
confidence: 99%
“… 116 , 117 In particular, Yang et al. 117 showed that those with ADPKD had a higher incidence of ST-elevation myocardial infarction (75% compared with 59%), sudden cardiac death (11.5% vs. 4.6%), need for coronary artery bypass grafting (7.7% vs. 5.4%) and higher overall mortality (13.5% vs. 6.2%). Most prior large ADPKD studies excluded patients with a history of ischemic heart disease and this may contribute to the relative paucity of data on ischemic cardiomyopathy in this group.…”
Section: Cardiac Manifestations In Adpkdmentioning
confidence: 99%